3,6-Dibromo-9-(4-tert-butylbenzyl)-9H-carbazole - Cao, Duan-Lin (International Union of Crystallography, 2008)
In the title compound, C(23)H(21)Br(2)N, which was synthesized by the N-alkylation of 1-tert-butyl-4-(chloromethyl)benzene with 3,6-dibromo-9H-carbazole, the asymmetric unit contains two unique molecules. Each carbazole ring system is essentially planar, with mean deviations of 0.0077 and 0.0089 Å for the two molecules. The carbazole planes make dihedral angles of 78.9 (2) and 81.8 (2)° with the planes of the respective benzene rings.